Kinetic studies of cathode degradation on PEM fuel cell short stack level undergoing freeze startups with different states of residual water and current draws - Liphardt, L.; Suematsu, K.; Grundmeier, Guido (International Journal of Hydrogen Energy)
Keywords: Energy Engineering and Power Technology; Condensed Matter Physics; Fuel Technology; Renewable Energy; Sustainability and the Environment

Initial Design Strategies and Their Effects on Sequential Model-Based Optimization: An Exploratory Case Study Based on BBOB - Bossek, Jakob; Doerr, Carola; Kerschke, Pascal (Proceedings of the Genetic and Evolutionary Computation Conference)
Sequential model-based optimization (SMBO) approaches are algorithms for solving problems that require computationally or otherwise expensive function evaluations. The key design principle of SMBO is a substitution of the true objective function by a surrogate, which is used to propose the point(s) to be evaluated next. SMBO algorithms are intrinsically modular, leaving the user with many important design choices. Significant research efforts go into understanding which settings perform best for which type of problems. Most works, however, focus on the choice of the model, the acquisition function, and the strategy used to optimize the latter. The choice of the initial sampling strategy, however, receives much less attention. Not surprisingly, quite diverging recommendations can be found in the literature. We analyze in this work how the size and the distribution of the initial sample influences the overall quality of the efficient global optimization (EGO) algorithm, a well-known SMBO approach. While, overall, small initial budgets using Halton sampling seem preferable, we also observe that the performance landscape is rather unstructured. We furthermore identify several situations in which EGO performs unfavorably against random sampling. Both observations indicate that an adaptive SMBO design could be beneficial, making SMBO an interesting test-bed for automated algorithm design.
Keywords: continuous black-box optimization; design of experiments; initial design; sequential model-based optimization

Further Extending the Dilution Range of the “Solvent-in-DES” Regime upon the Replacement of Water by an Organic Solvent with Hydrogen Bond Capabilities - Lopez Salas, Nieves; Vicent-Luna, J. M.; Posada, E.; Imberti, S.; Madero-Castro, R. M.; Calero, S.; Ania, C. O.; Jiménez-Riobóo, R. J.; Gutiérrez, M. C.; Ferrer, M. L.; del Monte, F. (ACS Sustainable Chemistry & Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Synergetic modulation of the electronic structure and hydrophilicity of nickel–iron hydroxide for efficient oxygen evolution by UV/ozone treatment - Pan, Ying; Wu, Yanfang; Hsain, H. Alex; Su, Ran; Cazorla, Claudio; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced OER performance of Ni(Fe) hydroxide through UV/ozone treatment.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Assessment of electrocatalytic activity through the lens of three surface area normalization techniques - Ren, Hangjuan; Pan, Ying; Sorrell, Charles C.; Du, Haiwei (Journal of Materials Chemistry A)
Electrocatalytic activities of electrodes for water splitting are assessed via geometric area, BET surface area and ECSA normalisations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Differentiability of the evolution map and Mackey continuity - Hanusch, Maximilian (Forum Mathematicum)
Keywords: regularity of Lie groups; differentiability of the evolution map

Looking at the “Water-in-Deep-Eutectic-Solvent” System: A Dilution Range for High Performance Eutectics - Lopez Salas, Nieves; Vicent-Luna, José Manuel; Imberti, Silvia; Posada, Elena; Roldán, María Jesús; Anta, Juan A.; Balestra, Salvador R. G.; Madero Castro, Rafael M.; Calero, Sofia; Jiménez-Riobóo, Rafael J.; Gutiérrez, María Concepción; Ferrer, María Luisa; et al. (ACS Sustainable Chemistry & Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

The value of signals: Do self-declaration and certification generate price premiums for organic and biodynamic wines? - Fanasch, Patrizia; Frick, Bernd (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

„A coupled phase field/diffusion model for upper and lower bainitic transformation” - Düsing, M.; Mahnken, R. (International Journal of Solids and Structures)
Bainite is a steel microstructure consisting of three phases, bainitic ferrite, austenite and carbides. It forms in two different morphologies, upper and lower bainite, where different diffusion mechanisms are dominant. The aim of this work is to simulate both transformations within a unified model. To this end, we extend an own previously published model for lower bainite with diffusion across the phase interface. As a central idea we introduce weighted Helmholtz energy functions and a weighted mobility tensor, respectively. The individual Helmholtz energy functions and mobility terms are related to the different diffusion mechanisms which are responsible for the formation of both morphologies. Two representative examples illustrate the capability of the coupled phase field/diffusion model and show the expected behaviour.
Keywords: Coupled phase field/diffusion model; Bainite; Multiphase field method; Cahn–Hilliard diffusion; Diffusion across the interface; Lower bainitic transformation; Upper bainitic transformation; Thermodynamic framework; Microforce balance

Political embeddedness and the diffusion of corporate social responsibility practices in China: A trade-off between financial and CSR performance? - Wang, Zhi; Reimsbach, Daniel; Braam, Geert (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Developing intercalation based anode materials for fluoride-ion batteries: topochemical reduction of Sr2TiO3F2via a hydride based defluorination process - Wissel, Kerstin; Dasgupta, Supratik; Benes, Alexander; Schoch, Roland; Bauer, Matthias; Witte, Ralf; Fortes, Andrew Dominic; Erdem, Emre; Rohrer, Jochen; Clemens, Oliver (Journal of Materials Chemistry A)
Sr2TiO3F2−x, a potential anode material for fluoride ion batteries, is prepared in the charged state via selective low-temperature defluorination.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Active site engineering by surface sulfurization for a highly efficient oxygen evolution reaction: a case study of Co3O4 electrocatalysts - Pan, Ying; Ren, Hangjuan; Du, Haiwei; Cao, Fuyang; Jiang, Yifeng; Du, Haojin; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced catalytic activity of Co3O4@CoSx through surface sulfurization.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Optimization of the energy supply in the plastics industry to reduce the primary energy demand - Dunkelberg, Heiko; Wagner, Johannes; Hannen, Conrad; Schlüter, Alexander; Phan, Long; Hesselbach, Jens; Lin, Cheng-Xian (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

Surface Cleaning and Modification by High Intense UV-Irradition for TiO2 Nanoparticle Films in Dye Sensitized Solar Cells - Kleine, A.; Hilleringmann, Ulrich (Renewable Energy and Power Quality Journal)
Keywords: Electrical and Electronic Engineering; Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment

Increasing the Efficiency of Solar Cells by Combining Silicon- and Dye Sensitized Devices - Ohms, B.; Kleine, A.; Hilleringmann, Ulrich (Renewable Energy and Power Quality)
Keywords: Electrical and Electronic Engineering; Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment

Validated Simulation of the Ultrasonic Wire Bonding Process - Unger, Andreas; Schemmel, Reinhard; Meyer, Tobias; Eacock, Florian; Eichwald, Paul; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (Wear Modeling in Copper Wire Wedge Bonding. IEEE CPMT Symposium Japan, 2016)
To increase quality and reliability of copper wire bonds, self-optimization is a promising technique. For the implementation of self-optimization for ultrasonic heavy copper wire bonding machines, a model of stick-slip motion between tool and wire and between wire and substrate during the bonding process is essential. Investigations confirm that both of these contacts do indeed show stick-slip movement in each period oscillation. In a first step, this paper shows the importance of modeling the stick-slip effect by determining, monitoring and analyzing amplitudes and phase angles of tooltip, wire and substrate experimentally during bonding via laser measurements. In a second step, the paper presents a dynamic model which has been parameterized using an iterative numerical parameter identification method. This model includes Archard’s wear approach in order to compute the lost volume of tool tip due to wear over the entire process time. A validation of the model by comparing measured and calculated amplitudes of tool tip and wire reveals high model quality. Then it is then possible to calculate the lifetime of the tool for different process parameters, i.e. values of normal force and ultrasonic voltage.
Keywords: the Ultrasonic Wire Bonding Process

Tailoring the textural properties of hierarchical porous carbons using deep eutectic solvents - Lopez Salas, Nieves; Carriazo, D.; Gutiérrez, M. C.; Ferrer, M. L.; Ania, C. O.; Rubio, F.; Tamayo, A.; Fierro, J. L. G.; del Monte, F. (Journal of Materials Chemistry A)
DESs containing resorcinol, urea and choline chloride allow the preparation of monolithic carbons with bicontinuous porous structures, the pore dimension of which can be easily tailored by the molar ratio of the components at the original DES.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

A holistic approach to energy efficiency assessment in plastic processing - Schlüter, Alexander; Rosano, Michele B. (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

Phosphorus-doped carbon–carbon nanotube hierarchical monoliths as true three-dimensional electrodes in supercapacitor cells - Patiño, Julián; Lopez Salas, Nieves; Gutiérrez, María C.; Carriazo, Daniel; Ferrer, M. Luisa; Monte, Francisco del (Journal of Materials Chemistry A)
Phosphorus-doped carbon–carbon nanotube hierarchical monoliths exhibiting energy densities of around 22.6 W h kg−1 at power densities of up to 10 kW kg−1 were capable of functioning as true three-dimensional electrodes in supercapacitor cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Nitrogen-doped carbons prepared from eutectic mixtures as metal-free oxygen reduction catalysts - Lopez Salas, Nieves; Gutiérrez, María C.; Ania, Conchi O.; Muñoz-Márquez, Miguel A.; Luisa Ferrer, M.; Monte, Francisco del (Journal of Materials Chemistry A)
Deep eutectic solvents (DESs) composed of resorcinol, either 2-cyanophenol or 4-cyanophenol, and choline chloride were used for the synthesis of hierarchical nitrogen-doped carbon molecular sieves.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry